Effect of taste masking technology on fast dissolving oral film: dissolution rate and bioavailability. (23rd May 2018) - Zhu, Ying; You, Xinru; Huang, Keqing; Raza, Faisal; Lu, Xin; Chen, Yuejian; Dhinakar, Arvind; Zhang, Yuan; Kang, Yang; Wu, Jun; Ge, Liang
Abstract: Fast dissolving oral film is a stamp-style, drug-loaded polymer film with rapid disintegration and dissolution. This new kind of drug delivery system requires effective taste masking technology. Suspension intermediate and liposome intermediate were prepared, respectively, for the formulation of two kinds of fast dissolving oral films with the aim of studying the effect of taste masking technology on the bioavailability of oral films. Loratadine was selected as the model drug. The surface pH of the films was close to neutral, avoiding oral mucosal irritation or side effects. The thickness of a 2 cm × 2 cm suspension oral film containing 10 mg of loratadine was 100 μ m. Electron microscope analysis showed that liposomes were spherical before and after re-dissolution, and drugs with obvious bitterness could be masked by the encapsulation of liposomes. Dissolution of the two films was superior to that of the commercial tablets. Rat pharmacokinetic experiments showed that the oral bioavailability of the suspension film was significantly higher than that of the commercial tablets, and the relative bioavailability of the suspension film was 175%. Liposomal film produced a certain amount of improvement in bioavailability, but lower than that of the suspension film.